1995
DOI: 10.1091/mbc.6.12.1743
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage matrix protein forms a type II collagen-independent filamentous network: analysis in primary cell cultures with a retrovirus expression system.

Abstract: Cartilage matrix protein (CMP) is expressed specifically in mature cartilage and consists of two von Willebrand factor A domains (CMP-A1 and CMP-A2) that are separated by an epidermal growth factor-like domain, and a coiled-coil tail domain at the carboxyl terminal end. We have shown previously that CMP interacts with type II collagencontaining fibrils in cartilage. In this study, we describe a type II collagen-independent CMP filament and we analyze the structural requirement for the formation of this type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
50
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 33 publications
6
50
0
2
Order By: Relevance
“…Similar results were obtained for the distribution of matrilin-1 in cultures of chicken chondrocytes, in which a more extended collagen-dependent network (21,25) and a pericellular, collagen-independent network were also described (21). Recent studies revealed functional differences between the two A domains of matrilin-1.…”
Section: Matrilin-3 Is Able To Form Homo-andsupporting
confidence: 72%
See 1 more Smart Citation
“…Similar results were obtained for the distribution of matrilin-1 in cultures of chicken chondrocytes, in which a more extended collagen-dependent network (21,25) and a pericellular, collagen-independent network were also described (21). Recent studies revealed functional differences between the two A domains of matrilin-1.…”
Section: Matrilin-3 Is Able To Form Homo-andsupporting
confidence: 72%
“…These extended fibrils could not be detected in the absence of ascorbate (Fig. 5B), conditions known to inhibit collagen secretion (21). Under those conditions, matrilin-3 was seen on the surface of individual cells or in network structures connecting adjacent cells (Fig.…”
Section: Recombinant Expression Of Matrilin-3mentioning
confidence: 90%
“…CMP forms two types of filamentous networks in the pericellular matrix: one that contains type II collagen and another that does not contain type II collagen (30). The collagen-independent CMP filaments may also serve as a scaffold for cell adhesion in vivo because CMP at high concentrations (10 -20 g/ml) enhanced cell spreading in the absence of type II collagen in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-p38 MAPK, anti-JNK1, anti-BCL-2, and protein A/G were purchased from Santa Cruz Biotechnology Inc (Santa Cruz, CA). Monoclonal antibodies including anti-CMP and anti-link protein were prepared as described previously (16 Cell Culture and Preparation of Cell Lysates-Primary chondrocyte cultures were established as described previously (1). Briefly, hypertrophic chondrocytes were obtained from the cephalic part of sterna cartilage from 17-day-old embryonic chickens, and prehypertrophic chondrocytes were obtained from the caudal part of the cartilage.…”
mentioning
confidence: 99%